Behavior of dynamic radial thrust acting on a vertical mixed flow pump impeller - Yuji KANEMORI; Yasuo HANDA (Nihon Kikai Gakkai ronbunshu, 2016)
Dynamic fluid forces acting on an impeller of a diffuser type mixed flow pump have been studied. The behavior of the thrust generated by the vortex occurrence in a pump intake sump was investigated. The force of distinct discontinuities such as hysteresis phenomenon from a pump hydraulic performance was measured. In pump partial load operation the radial thrust increases discontinuously because of the reverse flow at impeller inlet. The radial and axial thrust discontinuities occur at different threshold flow rates when increasing or decreasing the pump discharge flow thereby composing a hysteresis loop. Synchronous and non-synchronous components of radial thrust increase during the onset of reverse flow zones. A prediction method for dynamic radial thrust was derived based on Black's theory. Qualitative comparison with the measured experimental results for dynamic radial thrust showed reasonable agreement around pump best efficiency flow rate. The pump intake sump test apparatus, in which both an air-entrained surface vortex and a submerged vortex will occur, was employed and the radial thrust was measured. The level of radial thrust is dependent on the pump intake sump water level. The radial thrust begins to increase due to the occurrence of a full air core vortex to intake. When submerged as well as full air core continuous vortices occur, the radial thrust and the fluctuation of total pump head become abruptly large. The fluctuation of radial thrust becomes the highest when the impeller blade cutting the air-drawing large vortex imposes shock-like forces which generate not only an unbalance force but also nZ vane passing component.